Water and Health: products, materials, chemicals/mixtures and equipment used in contact with drinking water and protection of human health – in accordance with Order No 275/2012 - STOIAN, Irina; PARVU, Simona; NEAMTU, Andra; PETRE, Marta; NEAGU, Liliana; IORDACHE, Irina (One Health & Risk Management, 2022)
To ensure the safe hygiene of drinking water, four Member States of the European Union (France, Germany, the Netherlands and the United Kingdom) – known as 4MS - made arrangements in 2011 to work together on this important aspect of the regulatory framework.Currently, about twenty copper alloys are used in the safe transportation of clean drinking water to our homes and businesses. The copper industry has continuously tested different alloys for compatibility with new EU requirements and adapted the chemical composition of existing alloys. New alloys are currently being tested (after years of research) and submitted for approval and submitted by 4MS, they have committed to publish the documents, after their full agreement.Authorization of substances that are not on the positive list can lead to their rapid migration into the water and thus causing acute effects within the body (these may be irritating to the respiratory system , hence triggering asthma attacks; irritating to the skin , resulting in itchy skin, and rash such as dermatitis and papules) or may be released from the structure of the product over time, causing cumulative toxic effects (being ingested , these may cause gastrointestinal disorders; in kidneys, thesemay be associated with an increased risk of developing renal carcinomas).Toxic substances with a threshold effect are substances that become toxic only above a certain concentration (threshold) - cyanides or nitrates or various metals that are toxic above the threshold concentration, which can be reached gradually by the phenomenon of bioaccumulation. Genotoxic substances (arsenic, some synthetic organic substances, many halogenated organic compounds, some pesticides, etc.) are substances that produce harmful effects: carcinogenic (produce cancer), mutagenic (produce genetic mutations), or teratogenic (produce malformations), possibly in any concentration and for which it has not been possible to establish a threshold below which they are not harmful. The higher the risk, the higher the genotoxic substance, the more likely it is to attack more genes. The essential elements (selenium, fluoride, iodine, etc.) are the substances that must be part of the human diet. Some of them reach the body predominantly or exclusively through water and their lack or deficiency affect the health of the living organisms. At high concentrations, these elements can be harmful, such as toxic substances with a threshold effect.Drinking water quality is a key factor in health, according to the World Health Organization (WHO). High quality, clean and sufficient drinking water is essential for our daily life, drinking and food preparation. European Union policy ensures that water intended for human intake is consumed safely throughout its lifetime and this represents a high level of health protection. The protection of human health against any type of contamination of drinking water and the protection of public health is done primarily by reducing short-term or long-term exposure to risk factors posed by chemicals found in materials that come into contact with drinking water, whose values may exceed the CMA (maximum allowable concentration) set by the law. The contribution of the Commissions for materials in contact with drinking water by assessing the files is a very important endeavour. Improving the quality of life of the population and access to safe drinking water is a priority for us. The new European Drinking Water Directive has set out standards for drinking water quality, including in terms of materials, chemicals/mixtures and equipment used in contact with drinking water. The main objective still refers to the hygienic safety of drinking water.